Effects of Machine Parameters on Surface Roughness Using Response Surface Method in Drilling Process - Mohd , amran; Salmah, Siti; Hussein, Nur Izan Syahriah; Raja, Izamshah; Mohd , Hadzley; Sivarao, Subramonian; Kasim, Mohd Shahir; Sulaiman, Mohd Amri (2013)
The optimization of surface integrity in drilling process using response surface method (RSM) is presented. This paper investigates the effects of drilling parameter such as spindle speed, feed rate and drill diameter on the surface roughness and surface texture of drilled hole by applying RSM. There are three factors (spindle speed, feed rate and drill diameter)under investigation, therefore, by applying RSM there will be 20 experimental observations. The minimum surface roughness measured for the hole was 1.06 m of combination of 2000 rpm spindle speed, 78 mm/min feed rate and 2.5 mm drill diameter. While the maximum surface roughness of 2.59 m was measured of the combination of 250 rpm spindle speed, ,l53 mm/min feed rate and 3.5 mm drill diameter. One factor plot analysis found that the most significant parameter was spindle speed followed by drill diameter and feed rate. Thus, surface roughness decreased when increasing the spindle speed, feed rate and drill diameter. There were interactions between all the parameter of spindle speed, feed rate and drill diameter in drilling process under investigation.